Hubungan Kontrasepsi Hormonal, Lama Pemakaian, dan Penyakit Diabetes Militus terhadap Gangguan Menstruasi pada Wanita Usia Subur Di Wilayah Kerja UPTD Puskesmas Sukarami Kabupaten Muara Enim Tahun 2021 - Nova Sri Astuti; Yulizar Yulizar; Sri Handayani (Universitas Batanghari Jambi, 2022)
Menstrual disorders are conditions when the menstrual cycle experiences anomalies or abnormalities. WHO data in 2012 the prevalence of menstrual disorders in women was around 45%. This study was aimed at determining the relationships of hormonal contraception, duration of use and diabetes mellitus toward menstrual disorders in women of childbearing age in the Working Area of Sukarami Public Health Center (the regional technical implementation unit), Sungai Rotan District, Muara Enim Regency in 2021. This study was an analytical survey with a cross-sectional approach and it used chi-square statistical test. The population of this study was all the women of childbearing age, with a total 40 mothers who visited the Public Health Center. The result of the study showed that there was a significant relationship between hormonal contraception and menstrual disorders with p value 0.026 (0.05), duration of contraception use and menstrual disorders with p value 0.021 (0.05), diabetes mellitus and menstrual disorders with p value 0.016 (0.05). The results of the study whole be used as input for health workers especially at the Sukarami Public Health Center to provide counseling about menstrual disorders and improve health services to the community.